2018
DOI: 10.1111/edt.12446
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mouthguard design on retention and potential issues arising with usability in sport

Abstract: Background/Aims Mouthguard retention could potentially increase an athlete's motivation to wear the device, due to potential improvements in physical comfort. The aim of this study was to examine the retentive properties of selected customised mouthguard designs, during normal conditions (dry) and within the presence of artificial saliva (wet). Additionally, the correlation between thickness and retention was investigated. Material and Methods Six different custom mouthguard designs (MG1‐MG6) reported in previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 18 publications
2
23
1
2
Order By: Relevance
“…33 In most water polo players, the limited perceived benefit offered by anterior contact might be insufficient to counteract the greater discomfort due to increased mouthguard thickness. Although in vitro data show that mouthguards have better retention as they become thicker, 34 players in this study reported no differences between the conventional and occlusal-accommodated mouthguards. Therefore, the conventional custom-made mouthguard appears to offer a good balance between sufficient retention and tolerance.…”
Section: Discussioncontrasting
confidence: 69%
“…33 In most water polo players, the limited perceived benefit offered by anterior contact might be insufficient to counteract the greater discomfort due to increased mouthguard thickness. Although in vitro data show that mouthguards have better retention as they become thicker, 34 players in this study reported no differences between the conventional and occlusal-accommodated mouthguards. Therefore, the conventional custom-made mouthguard appears to offer a good balance between sufficient retention and tolerance.…”
Section: Discussioncontrasting
confidence: 69%
“…Several studies have also shown that the attitude towards mouthguards evolves after the experience of a dental trauma . Design and thickness are key factors for the wearability of mouthguards . Aesthetic considerations are due to subjective awareness, but poor retention and breathing problems can be addressed with a custom‐made mouthguard …”
Section: Discussionmentioning
confidence: 99%
“…The protectors inside the mouth must be aligned with the upper jaw. Therefore, a proper fit and high local retention throughout the physical activity constitute the design challenges to consider for the device to remain in the same position during the sports practice [20]. It is also noteworthy that the thickness through the length of the device may affect the final retention, comfort, and capacity of protection [21].…”
Section: Properties and Design Of Mouthguardsmentioning
confidence: 99%